A Case for Culturo-Techno-Contextual Approach for Enhanced Academic Achievement in STEM Education - Akintoye, Hakeem; Adam, Umar Ayotunde; Lameed, Soladoye Nurudeen; Bankole, Isaac Sewanu; Ayodeji, Benjamin (Journal of Educational Sciences, 2023)
The urgency to develop culturally and contextually responsive pedagogies in science education has become increasingly evident in recent times. In response, various teaching methods have been explored, showing successes in acquiring scientific knowledge. However, a more transformative approach is needed to fulfil the vision of the "Africa we want" as outlined in the African Union Commission's agenda 2063. This advocacy has led to the development of the Culturo-Techno-Contextual CTCA). The study aimed to conduct a documental analysis to evaluate the effectiveness of the CTCA in improving students' achievement in STEM subjects and explore teachers' perspectives on the efficacy of CTCA in science education. Qualitative approach, incorporating documentary analysis and interviews was employed. For the documentary analysis, a comprehensive search was conducted in electronic research databases from 2019 to 2023, using specific search terms related to CTCA and study design. The interview schedule involved a face-to-face interview with 8 teachers who had used CTCA to teach various STEM concepts. It was revealed that the CTCA possesses remarkable efficacy in enhancing students' academic achievement in STEM concepts. Also, the teachers showed positive perception towards CTCA. It was concluded that CTCA is a potent approach in improving students’ achievement in STEM subjects.